Mars One-Year Mission Craft - Claudio Bruno; Antonella Ingenito; Domenico Simone (Aerospace, 2023)
A human Mars mission is more challenging to astronauts than the Apollo mission because of travel time, life support requirements, and the space environment. Although plans for Mars exploration by NASA and SpaceX based on conventional rockets have been presented, there are considerations that suggest alternatives for the mid- or long-term. The purpose of this paper is to outline a fast mission enabled by advanced (nuclear) propulsion and by internationally shared technology. Whether the destination is the Mars surface or Phobos, for a chemical powered spacecraft, the round trip takes about 990 days, including a 480-day surface stay, compared to only 370 days, including a 41-day surface stay, for the nuclear-powered spacecraft assumed here. Since nuclear propulsion can provide higher speed than chemical, the radiation dose can be drastically reduced. The logistics of such a mission involve one or more cargo craft that must precede the astronauts. Ballistic entry into Mars’ atmosphere depends on accurate knowledge of its features, to date poorly known, that may result in uncertainty in landing coordinates. For a single vehicle, this is not critical, but for a human crew ballistic landing kilometers away from cargo is unacceptable: walking for anything but the shortest distance cannot be afforded with current space suits. In this context, the concept of a modest L/D maneuvering cargo glider based on the past Russian “Kliper” is recommended and developed to ensure landing within a hundred meters of each spacecraft. The crewed lander vehicle is based on the high L/D, inherently stable USAF FDL-7C/D hypersonic glider experience. In a similar approach, an exploration vehicle powered by in situ manufactured CO2 and silane is described that can explore the Martian surface much faster and efficiently than with rovers or rocket-powered ‘hoppers’.